2016
DOI: 10.1007/s10103-016-2124-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of femtosecond lasers for application of acupuncture therapy

Abstract: Acupuncture treatment utilizes the stimulation of metal acupuncture needles that are manually inserted into a living body. In the last decades, laser light has been used as an alternative to needles to stimulate acupuncture points. We previously reported suppression of myostatin (Mstn) gene expression in skeletal muscle by means of femtosecond laser (FL) irradiation, after electroacupuncture, in which acupuncture needles are stimulated with a low-frequency microcurrent. The purpose of the study here was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Through investigation of its effects on neuralgia, Butkovic and Tot (2017) found that laser needle-knife was an effective method of relieving hyperalgia and paralgesia. According to research conducted by Ohta et al (2017) in which the effects of laser electro-acupuncture on protein synthesis in mouse skeletal muscles were investigated, laser radiation was believed to significantly inhibit the protein expression of MSTN and increase the phosphorylation of P70S6K within the mTOR/S6signaling pathway. As described by Jittiwat (2007), who studied the impact of using a laser needle-knife on brain injury, cortical oxidation and the quantity of superoxide dismutase in the mitochondria of animals at the site of focal ischemic stroke, the volume of cerebral infarction reduced in the case of cerebral ischemia due to a decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Through investigation of its effects on neuralgia, Butkovic and Tot (2017) found that laser needle-knife was an effective method of relieving hyperalgia and paralgesia. According to research conducted by Ohta et al (2017) in which the effects of laser electro-acupuncture on protein synthesis in mouse skeletal muscles were investigated, laser radiation was believed to significantly inhibit the protein expression of MSTN and increase the phosphorylation of P70S6K within the mTOR/S6signaling pathway. As described by Jittiwat (2007), who studied the impact of using a laser needle-knife on brain injury, cortical oxidation and the quantity of superoxide dismutase in the mitochondria of animals at the site of focal ischemic stroke, the volume of cerebral infarction reduced in the case of cerebral ischemia due to a decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics of the impulsive force allowed us to realize several kinds of new manipulation for cells and proteins. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In addition to such cell manipulation, we considered the impulsive force can be utilized for the evaluation of intercellular adhesion strength. The need for evaluation at single-cell resolution is increased with progress in microscope imaging techniques.…”
Section: Intercellular Adhesion Estimated By the Impulsive Forcementioning
confidence: 99%
“…The impulsive force can be tuned to be over a million times larger than the force by the optical tweezers, though the force loading time is only a few microseconds. By virtue of the unique characteristics of the impulsive force, we have developed several types of manipulation methods for cells and proteins, 15) such as cell patterning, [16][17][18] photoporation, [19][20][21][22] cell stimulation, [23][24][25] cell sorting in a microchip 26,27) and protein crystallization. [28][29][30] Our methods realize high-speed and high-precision single-cell manipulation compared with other methods.…”
Section: Introductionmentioning
confidence: 99%